If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2m + 3t)(3m + -4t) = 0 Multiply (2m + 3t) * (3m + -4t) (2m * (3m + -4t) + 3t * (3m + -4t)) = 0 ((3m * 2m + -4t * 2m) + 3t * (3m + -4t)) = 0 Reorder the terms: ((-8mt + 6m2) + 3t * (3m + -4t)) = 0 ((-8mt + 6m2) + 3t * (3m + -4t)) = 0 (-8mt + 6m2 + (3m * 3t + -4t * 3t)) = 0 (-8mt + 6m2 + (9mt + -12t2)) = 0 Reorder the terms: (-8mt + 9mt + 6m2 + -12t2) = 0 Combine like terms: -8mt + 9mt = 1mt (1mt + 6m2 + -12t2) = 0 Solving 1mt + 6m2 + -12t2 = 0 Solving for variable 'm'. Factor a trinomial. (3m + -4t)(2m + 3t) = 0Subproblem 1
Set the factor '(3m + -4t)' equal to zero and attempt to solve: Simplifying 3m + -4t = 0 Solving 3m + -4t = 0 Move all terms containing m to the left, all other terms to the right. Add '4t' to each side of the equation. 3m + -4t + 4t = 0 + 4t Combine like terms: -4t + 4t = 0 3m + 0 = 0 + 4t 3m = 0 + 4t Remove the zero: 3m = 4t Divide each side by '3'. m = 1.333333333t Simplifying m = 1.333333333tSubproblem 2
Set the factor '(2m + 3t)' equal to zero and attempt to solve: Simplifying 2m + 3t = 0 Solving 2m + 3t = 0 Move all terms containing m to the left, all other terms to the right. Add '-3t' to each side of the equation. 2m + 3t + -3t = 0 + -3t Combine like terms: 3t + -3t = 0 2m + 0 = 0 + -3t 2m = 0 + -3t Remove the zero: 2m = -3t Divide each side by '2'. m = -1.5t Simplifying m = -1.5tSolution
m = {1.333333333t, -1.5t}
| y=6000(1+0.04)5 | | 9x-8=8x+1 | | x^3-13x^2-2x+26=0 | | 7-3x-(-5x+2)+1+7x=5x | | 2x+4x-9x+7= | | 5(20x+25)=925 | | 10*xy+90=72x | | 12y-5y-7+4= | | 10x-50=7x+1 | | x-(5-2x)=1+(2+x) | | 2+(-3)(4)-(-5)= | | 15=-7+44y | | -100=x^2-29x | | 10x=1+5x | | 14+12y=16+9y | | .25x+9=1 | | 28-7x=-28x-28 | | X-13.6=-16 | | 12x-42+3x=6(3x-9) | | -23+13n+47-5n=-28 | | 5.3+(w+1.2)= | | -2u+1.4=-0.6 | | 10x=5+1x | | -2(b+7)=3b+7-5b | | H=-16t^2+7t+28 | | 8x+5x+8+6= | | 8-1-(18-2)/8= | | X-2y=3z | | 31-(2x+3)=2(x+4)+x | | 90+x*86=45x+8 | | -5(w+3)=-7w-35 | | -20-f=20-6f+20 |